Radiosensitivity enhancement of human thyroid carcinoma cells by the inhibitors of histone deacetylase sodium butyrate and valproic acid - Perona, Marina (2018)
Radiotherapy is one of the leading treatments for clinical cancer therapy. External beam radiotherapy has been proposed as an adjuvant treatment for patients bearing differentiated thyroid cancer refractory to conventional therapy. Our purpose was to study the combined effect of HDAC inhibitors (HDACi) and ionizing irradiation in thyroid cancer cell lines (Nthy-ori 3-1, WRO, TPC-1 and 8505c). HDACi radiosensitized thyroid cancer cells as evidenced by the reduction of survival fraction, whereas they had no effect in the normal cells. HDACi enhanced radiation-induced cell death in WRO cells. Gamma-H2AX foci number increased and persisted long after ionizing exposure in the HDACi-treated cells (WRO and TPC-1). Moreover, the expression of the repair-related gene Ku80 was differentially modulated only in the cancer cells, by the compounds at the protein and/or mRNA levels. We present in vitro evidence that HDACi can enhance the radiosensitivity of human thyroid cancer cells.